An optimized temporally controlled Gal4 system in Drosophila reveals degeneration caused by adult-onset neuronal Vps13D knockdown - Rozich, Emily; Randolph, Lynsey K.; Insolera, Ryan (Frontiers in Neuroscience, 2023)
Mutations in the human gene VPS13D cause the adult-onset neurodegenerative disease ataxia. Our previous work showed that disruptions in the Vps13D gene in Drosophila neurons causes mitochondrial defects. However, developmental lethality caused by Vps13D loss limited our understanding of the long-term physiological effects of Vps13D perturbation in neurons. Here, we optimized a previously generated system to temporally knock down Vps13D expression precisely in adult Drosophila neurons using a modification to the Gal4/UAS system. Adult-onset activation of Gal4 was enacted using the chemically-inducible tool which fuses a destabilizationdomain to the Gal4 repressor Gal80 (Gal80-DD). Optimization of the Gal80-DD tool shows that feeding animals the DD-stabilizing drug trimethoprim (TMP) during development and rearing at a reduced temperature maximally represses Gal4 activity. Temperature shift and removal of TMP from the food after eclosion robustly activates Gal4 expression in adult neurons. Using the optimized Gal80-DD system, we find that adult-onset Vps13D RNAi expression in neurons causes the accumulation of mitophagy intermediates, progressive deficits in locomotor activity, early lethality, and brain vacuolization characteristic of neurodegeneration. The development of this optimized system allows us to more precisely examine the degenerative phenotypes caused by Vps13D disruption, and can likely be utilized in the future for other genes associated with neurological diseases whose manipulation causes developmental lethality in Drosophila.